2017
DOI: 10.21010/ajtcam.v14i4s.5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral Effects of Medicinal Plants in the Management of Dengue: A Systematic Review

Abstract: Background:Dengue is considered as an important arboviral disease. Safe, low-cost, and effective drugs that possess inhibitory activity against dengue virus (DENV) are mostly needed to try to combat the dengue infection worldwide. Medicinal plants have been considered as an important alternative to manage several diseases, such as dengue. As authors have demonstrated the antiviral effect of medicinal plants against DENV, the aim of this study was to review systematically the published research concerning the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…However, further studies are needed to confirm these observations. Several studies showed that polyphenols, triterpenes, anthraquinones, saponins, and polysaccharides that were isolated from natural plants can inhibit the replication of herpes viruses [27]. A large number of plant-derived and synthetic anti-HSV agents have also been described [4,28].…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies are needed to confirm these observations. Several studies showed that polyphenols, triterpenes, anthraquinones, saponins, and polysaccharides that were isolated from natural plants can inhibit the replication of herpes viruses [27]. A large number of plant-derived and synthetic anti-HSV agents have also been described [4,28].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of scientific studies, following guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA statement), was carried out [34] , [35] on the selected medicinal plants. Furthermore, the PubMed-NCBI database (http://www.ncbi.nlm.nih.gov/pubmed) was systematically searched for experimental trials and related bioassays.…”
Section: Methodsmentioning
confidence: 99%
“…Cleome spp., Lantana spp., and Lippia spp.) possess antiviral activity against yellow fever, and Dengue [76,81,[88][89]. These essential oils include spathulenol, bicyclogermacrene, β-caryophyllene, α-humulene, humulene epoxide II and phytol, germecrene-D, spathulenol, geranial, and limonene.…”
Section: Terpenoidsmentioning
confidence: 99%